SISTEM INFORMASI AKUNTANSI PENGGAJIAN PEGAWAI PADA SEKRETARIAT DPRD KOTA DEPOK - Farhan Musyaffa (2021)
A payroll accounting information system is needed to support the effectiveness of paying salaries at the Depok City DPRD Secretariat, an effort to minimize errors in payroll is to use a payroll accounting system which can make it easier to pay salaries to Depok City DPRD Secretariat employees, because errors in payroll can result in poor employee performance. decreased due to reduced employee motivation. Based on this description, this final project aims to describe the payroll accounting system applied to the Depok City DPRD Secretariat. This final project is a descriptive research with qualitative analysis methods and literature study, the final project data is obtained by using interview and documentation techniques. The results of the study indicate that the application of the payroll accounting system is sufficient both in terms of operations and recording. This is indicated by the use of applications and systems to carry out payroll procedures Keywords: System, Accounting, Salary, Employee